2013
DOI: 10.11622/smedj.2013078
|View full text |Cite
|
Sign up to set email alerts
|

Immune response in infants after universal hepatitis B vaccination: a community-based study in Malaysia

Abstract: CONClUSIONThe proportion of Malaysian mothers who are positive for HBsAg remains high. The three-shot hepatitis B vaccine, given as part of universal vaccination against hepatitis B, provides adequate anti-HBs in the vast majority of infants in a community setting in Malaysia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The study by Cheang et al also reported seroprotection rates at year 1 in 59 preterm infants. The seroprotection rate at year 1 was 98.3% in preterm infants versus 96.4% in infants born at term [28].…”
Section: Standard Schedule and Pediatric Dosementioning
confidence: 89%
See 1 more Smart Citation
“…The study by Cheang et al also reported seroprotection rates at year 1 in 59 preterm infants. The seroprotection rate at year 1 was 98.3% in preterm infants versus 96.4% in infants born at term [28].…”
Section: Standard Schedule and Pediatric Dosementioning
confidence: 89%
“…In children 30-40 months of age vaccinated from birth, 83.8% continued to have anti-HBs antibodies ≥10 mIU/ml [27]. Cheang et al reported 96.4% seroprotection 1-year post-vaccination of newborn term infants [28] (data presented in Table 4). The blood sampling time point is given in months unless otherwise indicated.…”
Section: Standard Schedule and Pediatric Dosementioning
confidence: 99%
“…This apparent nonresponse could be due to many things including genetic factors, malnutrition or other illness, documentation errors, expired vaccine, or poor vaccination technique. Some individuals might have had no initial serologic response to vaccination; others might have had initially adequate antibody levels that waned over time . On the other hand, since no interval between series completion and testing was shorter than 5 months, the nonresponse is unlikely to be attributable to a postvaccination gap during which provoked immune systems were not yet producing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The HBsAg detection rate was 2.5% among those born in 1985 (before the implementation of universal infant vaccination), which declined to 0.4% among those born in 1996. 7 8 In another study among the 2,923 new student intakes in the Faculties of Medicine and Dentistry, University of Malaya, from 2005 to 2011, the overall HBsAg prevalence was 0.62%. The HBsAg prevalence rate was 1.08% (15/1,390) among those born before 1989 and only 0.20% (3/1,533) among those born in or after 1989.…”
Section: Past and Presentmentioning
confidence: 99%